Obese and non-obese polycystic ovarian syndrome: comparison of clinical, metabolic, hormonal parameter and their differential response to oral ovulation induction drugs - Shirin; Goyal, Ritu; Singh, Saranpal; Chander, Shafak (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Polycystic ovarian syndrome (PCOS) is a complex disorder characterized by hyperandrogenism, menstrual irregularities, and polycystic ovaries. The present study compared obese and non-obese PCOS patients in terms of clinical, metabolic, and hormonal parameters, as well as their response to oral ovulation induction drugs. Methods: This study was conducted in the Department of Obstetrics and Gynaecology, AIMSR Bathinda, over one year after approval from the Institutional Ethics Committee. Women with PCOS presenting with infertility were enrolled. Patients were categorized into obese and non-obese groups, and their clinical, metabolic, and hormonal profiles were compared. Data were recorded in Microsoft Excel and analysed using SPSS software. Results: The mean age was 25.3 years in the obese group and 26.1 years in the non-obese group. Mean fasting insulin levels were higher in obese patients (25.1 µIU/ml) compared to non-obese (15.9 µIU/ml). Similarly, insulin resistance and HOMA-IR values were significantly greater in the obese group. Mean testosterone levels were slightly higher in obese patients (58.3 ng/dl vs. 55.4 ng/dl). Conception rates following oral ovulation induction were significantly lower in obese women (30.6%) than in non-obese women (76.3%). Conclusions: Obese women with PCOS are at higher risk of metabolic derangements and exhibit poorer responsiveness to ovulation induction therapy. Early identification and targeted weight management strategies may not only prevent adverse outcomes but also improve fertility outcomes in this population.